SPIRITUALITY IN WORKPLACE, INDIVIDUAL SPIRITUALITY AND WORK BEHAVIOUR: THE STUDY OF HIGHER EDUCATION IN INDONESIA - Fitri Wulandari (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
Spirituality in the workplace include feeling connected to the community, the meaningfulness of the work, the ability to express their feelings and ability to work independently, have the power of doing work believed to be correct. This study seeks to analyze spirituality in the workplace and individual spirituality on the behavior of employees working at universities in Indonesia.The samples of the study are employees who work at universities in Surakarta with a sample of 132 employees. Data is analyzed using multiple regressions. The result of regression analysis showed that the concept of spirituality in the workplace include feelings of community teams, inner life and meaningful work affect on work behavior (job satisfaction, organizational commitment and job involvement). The results of this study indicate that there is no significant effect between the communities at work on job satisfaction. While the inner variable life, Meaningful in work and Individual Spirituality significantly influences job satisfaction. There was no significant effect between community at work and meaning at work on job involvement. While the inner variable life and Individual Spirituality significantly influences job involvement. There was no significant effect between the meanings at work to organization commitment. While the inner life variable, community at work and individual spirituality significantly influence organization commitment. Employees feel that life is full of hope in the future, and spiritual values also includes in making life choices. Employees at the college considers that his work has a deeper meaning than other jobs because they relate to the services to education and a strong desire to express spiritual practices in working life.Spiritualitas di tempat kerja termasuk merasa diterima oleh komunitas, kebermaknaan pekerjaan, kemampuan untuk mengekspresikan perasaan dan kemampuan untuk bekerja secara mandiri, serta memiliki kekuatan untuk melakukan pekerjaan yang diyakini benar. Penelitian ini bertujuan untuk menganalisis spiritualitas di tempat kerja dan spiritualitas individu pada perilaku karyawan yang bekerja di berbagai universitas di Indonesia . Sampel penelitian ini adalah karyawan yang bekerja di universitas di Surakarta dengan sampel sebanyak 132 karyawan. Data dianalisis dengan menggunakan regresi berganda. Hasil analisis regresi menunjukkan bahwa konsep spiritualitas di tempat kerja meliputi perasaan diterima oleh komunitas, kehidupan batin dan pekerjaan yang berarti mempengaruhi perilaku kerja (kepuasan kerja, komitmen organisasi, dan keterlibatan kerja). Hasil penelitian ini menunjukkan bahwa tidak ada pengaruh yang signifikan antara komunitas di tempat kerja terhadap kepuasan kerja. Sementara variabel kehidupan batin, merasa berarti dalam pekerjaan dan spiritualitas individu berpengaruh secara signifikan terhadap kepuasan kerja. Tidak ada pengaruh yang signifikan antara komunitas di tempat kerja dan makna bekerja pada keterlibatan kerja. Sementara variabel kehidupan batin dan Individu spiritualitas berpengaruh secara signifikan terhadap keterlibatan kerja. Tidak ada pengaruh yang signifikan antara makna bekerja untuk komitmen organisasi. Sedangkan variabel kehidupan batin, komunitas di tempat kerja dan spiritualitas individu berpengaruh signifikan terhadap komitmen organisasi. Para karyawan merasa bahwa hidup penuh harapan di masa depan, dan nilai-nilai spiritual termasuk di dalamnya adalah membuat pilihan hidup. Karyawan di perguruan tinggi menganggap bahwa karya memiliki arti yang lebih mendalam daripada pekerjaan lain karena pekerjaan yang berhubungan dengan layanan pendidikan dan keinginan yang kuat untuk mengekspresikan praktik spiritual dalam kehidupan kerja.